Low serum creatinine predicts risk for type 2 diabetes. Issue 6 (9th May 2018) - Bao, Xue; Gu, Yeqing; Zhang, Qing; Liu, Li; Meng, Ge; Wu, Hongmei; Xia, Yang; Shi, Hongbin; Wang, Honglei; Sun, Shaomei; Wang, Xing; Zhou, Ming; et al.
Abstract: Aims: As an insulin target tissue, skeletal muscle is inversely related to type 2 diabetes mellitus (T2DM). Serum creatinine originates mainly from creatine in muscle and is considered as a reliable surrogate marker for muscle mass in apparently healthy subjects. It is therefore hypothesized that low serum creatinine could effectively predict increased risk of T2DM. Yet information is scarce regarding the longitudinal relationship between serum creatinine and T2DM. This study aims to investigate this relation in a large general population of both men and women. Methods: A prospective cohort study (n = 57 587; follow‐up range: 1‐9 years, mean: 3.57 years, 95% confidence interval: 3.55‐3.58 years) was conducted in a general population sample from Tianjin, China. Multivariable Cox proportional hazards regression models were used to assess the relationship between baseline serum creatinine and the risk of developing T2DM (as defined by the American Diabetes Association criteria). Results: During the follow‐up period, 2017 subjects developed T2DM. The multivariate‐adjusted hazard ratios (95% confidence interval) for T2DM incidence across quintiles of serum creatinine were 1.00 (reference), 0.86 (0.75, 0.99), 0.82 (0.72, 0.94), 0.85 (0.74, 0.97), and 0.77 (0.67, 0.89; P for trend <.01). Similar results were observed in both sexes (interaction P = .56). Conclusions: These findings indicate that serum creatinine concentration is inversely related to incident T2DM in both men and women. Measuring serum creatinine may assist in the early detection of individuals at high risk of developing T2DM.